Methodology for quantitative assessment of combat casualty care. (April 2019) - Xynidis, Michael A.; Goldiez, Brian F.; Norfleet, Jack E.; Rothstein, Nina
Evaluating proficiency in simulation-based combat casualty training includes the assessment of hands-on training with mannequins through instructor observation. The evaluation process is error-prone due to high student–instructor ratios as well as the subjective nature of the evaluation process. Other logistical inconsistencies, such as the short amount of time to observe individual student performance, can lessen training effectiveness as well. The simulation-based methodology described in this article addresses these challenges by way of quantitative assessment of training effectiveness in combat casualty training. The methodology discusses adaptation of Lempel–Ziv (LZ) complexity indexing to quantify psychomotor activity that is otherwise only subjectively estimated by an instructor. LZ indexing has been successfully used to assess proficiency in related studies of simulation-based training conducted by Bann et al. at the Imperial College of Science Technology and Medicine in London, and more recently by Watson at the University of North Carolina at Chapel Hill. This type of analysis has been applied to using simulation as a tool to assess not only mastery of a task, but as a method to assess whether a particular simulator and training approach actually works. Data have been gathered from nearly 100 military combat medic trainees at Joint Base Lewis McChord Medical Simulation Training Center. Participant hand-acceleration data from an emergency surgical cricothyrotomy reveals a statistically significant difference in ability between expertise levels. The higher the LZ scores and self-reported expertise level, the better the participant performed. The results show that when presented with demographic and video performance-based data, it is possible to gauge experience by applying LZ scoring to motion data. The methodology provides an objective measure that complements the subjective component of simulation-based cricothyrotomy training assessments. Further study is needed to determine whether this methodology would provide similar assessment advantages in other medical training in which speed and accuracy would be significant factors in determining procedural expertise.